Sinergi Pembangunan Wisata Bahari Berkelanjutan dalam Rangka Mewujudkan Visi Maritim 2024 di Pulau Nusa Penida, Klungkung, Bali - Dewi, Nyoman Diah Utari; Widanti, Ni Putu Tirka; Sumada, I Made; Widnyani, Ida Ayu Putu Sri (Universitas Medan Area, 2024)
This research explores the synergy of sustainable marine tourism development in realizing the 2024 maritime vision on Nusa Penida Island, Klungkung, Bali, as well as the factors that affect it. The method used is a literature study with qualitative descriptive analysis. The results show that the synergy is achieved through communication and coordination of Indonesia's maritime vision with the implementation of optimization of marine tourism development under the Indonesian Marine Policy Action Plan 2021-2025 and Presidential Regulation Number 34 of 2022. Tourism in Bali has an economic impact on local communities, but its distribution needs to be more evenly distributed. Social, economic, and cultural tourism provides opportunities to utilize local potential with the participation of policy stakeholders. The tourism sector encourages the development of infrastructure and educational institutions, increasing human resources in the field of tourism. Factors influencing the synergy of marine tourism development include Indonesia's maritime history and politics, maritime biological and non-biological resources, socio-cultural factors, and maritime industry and economy. Recommendations include improving the marine ecotourism product program, multi-stakeholder involvement in planning, and the establishment of a special department in the Ministry of Tourism to focus on developing sustainable marine tourism to realize the 2024 maritime vision.